Phytochemical Composition of Talinum triangulare (Water Leaf) Leaves - Aja, P.M.; Okaka, A.N.C.; Onu, P.N.; Ibiam, U.; Urako, A.J. (Pakistan Journal of Nutrition, 2010)
The qualitative and quantitative analyses of Talinum triangulare (water leaf) leaf which is commonly used as vegetable in Nigeria were carried out on both dry and wet samples. The result of dry and wet samples revealed the presence of bioactive compounds namely flavonoids (69.80±4.42 mg/100 g and 58.33 ± 9.00 mg/100 g), alkaloids (55.56±5.00 mg/100 g and 13.89±5.00 mg/100 g), saponins (1.48±0.20 mg/100 g and 1.37±0.60 mg/100 g) and tannins (1.44±0.73 mg/100 g and 1.09±0.26 mg/100 g) respectively. The results indicate that the leaves contain an appreciable amount of bioactive compounds. Medically the presence of these phytochemicals explains the use of this vegetable in ethnomedicine for the management of various ailments.